2007
DOI: 10.1093/hmg/ddm311
|View full text |Cite
|
Sign up to set email alerts
|

Soluble polyglutamine oligomers formed prior to inclusion body formation are cytotoxic

Abstract: Expanded polyglutamine (polyQ) repeats cause neurodegenerative disorders, but their cytotoxic structures remain to be elucidated. Although soluble polyQ oligomers have been proposed as a cytotoxic structure, the cytotoxicity of soluble polyQ oligomers, not inclusion bodies (IBs), has not been proven in living cells. To clarify the cytotoxicity of soluble polyQ oligomers, we carried our fluorescence resonance energy transfer (FRET) confocal microscopy and distinguished oligomers from monomers and IBs in a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
180
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(208 citation statements)
references
References 44 publications
15
180
3
Order By: Relevance
“…This indicates that collapse of proteostasis might have occurred before the appearance of detectable Htt-97Q aggregates. This observation is in line with other studies that suggest a role of the oligomeric species of the mutant Htt protein in proteostasis imbalance and cellular toxicity (Arrasate et al, 2004;Bodner et al, 2006;Miller et al, 2010;Saudou et al, 1998;Takahashi et al, 2008). However, after the mutant Htt formed visible aggregates, the aggregation of FlucDM-EGFP became more severe and rapid which may suggest that aggregation of Htt continues to impose a challenge on the proteostasis machinery of cells.…”
Section: V42 Analysis Of Proteostasis Collapse By Huntingtin Proteinsupporting
confidence: 91%
See 2 more Smart Citations
“…This indicates that collapse of proteostasis might have occurred before the appearance of detectable Htt-97Q aggregates. This observation is in line with other studies that suggest a role of the oligomeric species of the mutant Htt protein in proteostasis imbalance and cellular toxicity (Arrasate et al, 2004;Bodner et al, 2006;Miller et al, 2010;Saudou et al, 1998;Takahashi et al, 2008). However, after the mutant Htt formed visible aggregates, the aggregation of FlucDM-EGFP became more severe and rapid which may suggest that aggregation of Htt continues to impose a challenge on the proteostasis machinery of cells.…”
Section: V42 Analysis Of Proteostasis Collapse By Huntingtin Proteinsupporting
confidence: 91%
“…A considerable body of experimental evidence suggests that formation of Htt inclusions is a protective mechanism, employed by cells to sequester potentially dangerous soluble oligomers of misfolded Htt (Arrasate et al, 2004;Bodner et al, 2006;Miller et al, 2010;Takahashi et al, 2008). This sequestration may reduce the number of exposed regions in mutant Htt that otherwise would titrate away cellular folding factors, putting the folding of the metastable proteome in jeopardy (Gidalevitz et al, 2006;Satyal et al, 2000).…”
Section: Ii431 Huntington's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies reported that the amount of polyQ protein inclusions does not correlate with neurodegeneration or that these inclusions are even protective, oligomeric species of misfolded polyQ proteins have been suggested as the principal culprit of neurodegeneration (6,35). In other protein-misfolding neurodegenerative diseases, soluble oligomers composed of A␤ or ␣-synuclein have also been shown to exert cytotoxicity, suggesting the intrinsic toxicity of oligomeric structures, regardless of their primary amino acid sequences (36).…”
Section: Discussionmentioning
confidence: 99%
“…PolyQ proteins are prone to misfold, oligomerize, and form aggregates and eventually accumulate as inclusion bodies in affected neurons (2,3). Whereas the formation of polyQ protein inclusion bodies is believed to be protective, by sequestering the toxic polyQ proteins (4), the intermediate structures formed during the aggregation process, such as monomers or oligomers, are reported to be more toxic for the cells, leading to neuronal dysfunction or neuronal cell death (5,6). The polyQ diseases are thus considered as one of the protein-folding diseases, together with Alzheimer disease, Parkinson disease, and ALS.…”
mentioning
confidence: 99%